Association between sitting time and cardiovascular risk factors in adolescents: a sectional study - Rodrigo de Oliveira Barbosa; Lorena Barreto Fonseca da Mata; Jadson Márcio da Silva; Gessika Castilho dos Santos; Renan Camargo Correa; Rodrigo Bozza; Wagner de Campos; Antônio Stabelini Neto (Instituto Brasileiro de Pesquisa e Ensino em Fisiologia do Exercício, 2022)
The present study aimed to analyze the association between sitting time and cardiovascular risk factors in Brazilian adolescents. The sample consisted of 1,777 adolescents (927 female). Sitting time was assessed by the Bouchard record. The risk factors evaluated were systolic blood pressure (SBP), diastolic blood pressure (DBP), and waist circumference (WC). The descriptions of continuous data are presented in values of mean and standard deviation. Student t test for independent groups. To verify the association between sitting time and measures of interest, multiple linear regression was applied. For data analysis, the statistical package SPSS version 22.0 was used and the significance was set at p<0.05. For males, a positive association was found between sitting time and SBP (β=0.136; p<0.001), DBP (β=0.073; p<0.001), and WC (β=0.086; p<0.001). After adjusting the sitting time by age, a significant positive association was found between sitting time and SBP (β=0.126; p<0.001) and WC (β=0.077; p<0.001). For females, no statistically significant associations were observed between sitting time and cardiovascular risk factors. It can be concluded that the time spent sitting in male adolescents negatively affects the cardiovascular risk factors analyzed, and to minimize future health risks, it is important to develop strategies aimed at reducing sitting time.